2017
DOI: 10.1098/rsif.2017.0364
|View full text |Cite
|
Sign up to set email alerts
|

Very weak oscillating magnetic field disrupts the magnetic compass of songbird migrants

Abstract: Previously, it has been shown that long-distance migrants, garden warblers (), were disoriented in the presence of narrow-band oscillating magnetic field (1.403 MHz OMF, 190 nT) during autumn migration. This agrees with the data of previous experiments with European robins (). In this study, we report the results of experiments with garden warblers tested under a 1.403 MHz OMF with various amplitudes (∼0.4, 1, ∼2.4, 7 and 20 nT). We found that the ability of garden warblers to orient in round arenas using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 54 publications
(98 reference statements)
5
28
1
Order By: Relevance
“…It was identical for the control and experimental conditions; furthermore, at the rural testing site on the Courish Spit the anthropogenic noise is likely to have been very low, as suggested e.g. by the functional magnetic compass observed in garden warblers when tested under control conditions at the same site [24,25].…”
Section: Experimental Birds and Sitementioning
confidence: 89%
See 1 more Smart Citation
“…It was identical for the control and experimental conditions; furthermore, at the rural testing site on the Courish Spit the anthropogenic noise is likely to have been very low, as suggested e.g. by the functional magnetic compass observed in garden warblers when tested under control conditions at the same site [24,25].…”
Section: Experimental Birds and Sitementioning
confidence: 89%
“…The birds were provided with food (mealworms) and water ad libitum. We did not measure the background electromagnetic noise level, which is important for the functionality of the magnetic compass in European robins and garden warblers [23,24]. It was identical for the control and experimental conditions; furthermore, at the rural testing site on the Courish Spit the anthropogenic noise is likely to have been very low, as suggested e.g.…”
Section: Experimental Birds and Sitementioning
confidence: 99%
“…Previously, RF intensities of 48–400 nT were shown to influence animal magnetic orientation behaviour (for review see Hiscock et al., ). Recent studies demonstrated an effect of much weaker (anthropogenic) RF fields in the low MHz range with strengths of about 10 nT (Engels et al., ; Pakhomov et al., ), and even lower intensities of broadband RF noise of 1 nT are discussed to influence magnetosensitive abilities of birds (Engels et al., ). In our study, intensities of 0.3 nT up to 10 nT at the highest peak (0.4 MHz) (control condition) seemed to have no influence on the magnetic orientation of Roborovski hamsters, but additional slight increases of 0.3–2 nT, when the coil system was switched on, seemed to disturb the hamster's orientation abilities.…”
Section: Discussionmentioning
confidence: 99%
“…This applies to migrants during migratory orientation [2124] as well as to directionally trained non-migrants such as Domestic Chickens [25] and Zebra Finches [26]. The Larmor frequency, that is, the frequency of the electron, proved most effective and disrupts orientation at very low intensities [27]; this has been independently confirmed by [23,28]. Reports of the opposite [24] are inconclusive because of methodological short-comings (use of metallic test cages that not only shield but also reflect and distort radiofrequency fields so that the conditions become undefined).…”
Section: Magnetic Compass: Starting Out With Radical Pair Processesmentioning
confidence: 94%